Benefits of local food system survey experience for participants and stakeholders: A case study of Akita, Japan - Ota, Kazuhiko; Taniguchi, Yoshimitsu; McGreevy, Steven R. (Frontiers in Sustainability, 2022)
This paper presents the results of interviews with seminar participants, seminar providers, and local stakeholders as local stakeholders seminar supporters on the seminar's impact on sustainability transitions in local food systems, which was conducted jointly by the research project and high schools. The seminar was conducted in 2017 at a high school in Noshiro, Akita Prefecture, Japan, at the request of one of the students and was named the "Transition Seminar. The seminar was held for over half a year (8 sessions in total) for about 30 high school students who requested it, with the theme of transforming the local food system in Noshiro City. Participants developed a vision of a desirable local food system under the theme of "the community's ideal food system 30 years from now," conducted fieldwork surveys, planned to realize the vision, and made policy proposals to the mayor of Noshiro. After the seminar, effectiveness measurements based on transformative learning theory revealed that the fieldwork survey experience, in particular, had a long-term impact on participants' understanding of and ability to reflect on the food system and policies in the Noshiro area. In addition, interviews conducted in 2019 confirmed various secondary effects, including increased interest and networking among participating high school students, teachers, and stakeholders. Complex social issues, such as improving local food systems, cannot be solved due to their dynamic and nonlinear nature. Through recursive cycles of action, research, and learning, this case study underscores the need for innovation that directs the complex context itself in a particular desired direction over time within a framework of co-evolution.